Calculations of terminal velocity for particles of any sphericity - García, Cézar; Sarmiento, Carmen (Rev. Téc. Fac. Ing. Univ. Zulia)
The knowledge of terminal velocity in fluid-solid systems is important for engineering design of equipment separations such as setting, hydraulic classification, fluidized beds, and others. The present technical note provides a straightforward calculation of terminal velocity when the physical properties are known for the fluid-solid system at the operating conditions. The proposed method results valid for the Reynolds Number between 0.1 and 10.000 and sphericity factors between 1.0 and 0.125.